Films Inspired by Actuality from the Communist Period as Historical Documents (Book Review: Ion Indolean, Opinie, prudenţă şi cenzură: Filmul de actualitate în România comunistă (1965-1989) [Opinion, Prudence and Censorship: Actuality Cinema in Communist Romania (1965-1989)], Cluj-Napoca, Mega Publishing House, 2023) - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
This solid, comprehensive book deals with a topic of great interest for film studies in Romania from an original perspective. It is about the actuality cinema during the Ceausescu regime, a theme that is quite frequently addressed in Romanian academic and non-academic research, but rarely treated convincingly and from truly innovative perspectives. In terms of content, Ion Indolean’s book succeeds in providing a wealth of unpublished factual information, well systematized in three parts of three chapters each, framed by the Introduction and Conclusions, and put into a convincing network of meanings. Part I. Film Production during the Ceausescu Regime focuses on the issue of creation, Part II. Films Produced during the Ceausescu Regime focuses on cinematographic works of art in their specific structures, while Part III. Promotion and censorship of films during the Ceausescu regime focuses on the issue of public reception of films after the obligatory stage of censorship commissions. As we can see, Ion Indolean borrows a classical structure of the discourse on film and art (creation-work-reception), but nuances it, adapting it to the specificities of cinema, especially to the context so characteristic of Romanian cinema under communism.